Case Report: A case of traumatic subgaleal hematoma with delayed massive exophthalmos - Lee, Hui Jae; Jung, JaeHwan; Joo, Taesung; Park, In-Ki; Koh, Jun Seok; Kang, Min Seok; Shin, Jae-Ho (Frontiers in Surgery, 2025)
Progressive exophthalmos occurring after minor trauma is very rare, it is important to consider subgaleal hematoma in the differential diagnosis. If diagnosis is delayed, permanent vision loss may occur due to optic nerve damage or corneal damage due to pressure, so performing decompression surgery at an appropriate time is effective in preventing blindness. A 16-year-old male patient with Lennox-Gastaut syndrome and developmental disability was admitted to the hospital 2 weeks after a head injury due to increased swelling and ecchymosis of left eyelid and suspicion of compressive optic neuropathy of the left eye due to massive exophthalmos. Visual acuity measurement was not possible due to the patient's condition., and the intraocular pressure in the left eye was 20 mmHg. The pupil size in both eyes was the same, and there was a pupil reflex in the left eye, and there were no abnormal findings in the blood coagulation test. Computed tomography (CT) showed a subperiosteal hematoma in the left orbit and left eye severe proptosis and deviation. To control intraocular pressure and relieve exposure keratopathy, the orbital hematoma was removed through a sub-brow incision, and a lateral canthotomy was performed, and a drain was installed to drain blood accumulated in the orbit under general anesthesia. Orbital CT taken for follow-up observation showed that the hematoma had decreased compared to the day of visit. Regarding the subgaleal hematoma, hematoma was aspirated three times at the neurosurgery department. After surgery, ointments for exposure keratopathy. During follow-up, corneal transparency was maintained and visual acuity was confirmed to be intact by VEP (Visual Evoked Potential).